Redesain Strategi Pembelajaran PAI Melalui Integrasi AI Dan Pendekatan Humanistik - Nabila Rahmalia; Alfiatus Sakbana; Ahmad Fuad Abdul Baqi (Education Reserach Center, 2026)
The development of Artificial Intelligence (AI) provides new opportunities for redesigning Islamic Religious Education (PAI) learning strategies to become more effective and relevant to the needs of the digital era. This study aims to analyze and formulate a concept for redesigning PAI learning strategies through the integration of AI with a humanistic approach in order to improve the quality of learning processes and outcomes, particularly in strengthening students’ character and spiritual values. This research employs a literature study method by reviewing various scientific journals, books, and documents related to educational technology, PAI learning, humanistic theory, and the application of AI in education. The findings indicate that the use of AI supports personalized learning, provides broader access to learning resources, enhances evaluation effectiveness, and strengthens teachers’ creativity in designing interactive learning experiences. Meanwhile, the humanistic approach ensures that the educational process continues to position students as the central subjects, emphasizing empathy, learning freedom, internalization of Islamic values, and character development. The integration of both elements results in a PAI learning model that is adaptive, humanistic, and contextual to the challenges of the 21st century. Therefore, redesigning PAI learning strategies based on AI and a humanistic approach becomes a strategic alternative in realizing innovative, meaningful, and sustainable Islamic education.